The Effect of High Pressure Processing on Textural, Bioactive and Digestibility Properties of Cooked Kimberley Large Kabuli Chickpeas - Chatur, Prakhar; Johnson, Stuart; Coorey, Ranil; Bhattarai, Rewati Raman; Bennett, Sarita Jane (Frontiers in Nutrition, 2022)
High pressure processing is a non-thermal method for preservation of various foods while retaining nutritional value and can be utilised for the development of ready-to-eat products. This original research investigated the effects of high pressure processing for development of a ready-to eat chickpea product using Australian kabuli chickpeas. Three pressure levels (200, 400, 600 MPA) and two treatment times (1 and 5 min) were selected to provide six distinct samples. When compared to the conventionally cooked chickpeas, high pressure processed chickpeas had a more desirable texture due to decrease in firmness, chewiness and gumminess. The general nutrient composition and individual mineral content were not affected by high pressure processing, however a significant increase in the slowly digestible starch from 50.53- 60.92 g/ 100 g starch and a concomitant decrease in rapidly digestible starch (11.10- 8.73 g/ 100g starch) as well as resistant starch (50.53- 30.35 g/ 100g starch) content was observed. Increased starch digestibility due to high pressure processing was recorded, whereas in vitro protein digestibility was unaffected. Significant effects of high pressure processing on the polyphenol content and antioxidant activities (DPPH, ABTS and ORAC) were observed, with the sample treated at the highest pressure for the longest duration (600 MPa, 5min) showing the lowest values. These findings suggest that high pressure processing could be utilised to produce a functional, ready to eat kabuli chickpea product with increased levels of beneficial slowly digestible starch.